Learning Motivation in Students in Online Lectures Reviewed from Social Support - Astuty, Helda Azmy; Rasyid, Miranti; Suhesty, Aulia (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
In the online classroom, students were often faced with different learning challenges than before, so this requires a higher learning motivation compared to studying in the class. One of the biggest challenges faced by students during the online learning period is limited interaction, so they only rely on the internet network to complete assignments. Because of limited interaction, students find it difficult to carry out discussions and learning that is less understandable, so this causes them to be less motivated in learning. This study aims to determine the relationship between social support and learning motivation in students in online lectures. This research method used a quantitative approach. The subjects in this study were 100 students of the Faculty of Social and Political Sciences, Mulawarman University class 2018, 2019, 2020, 2021 who were selected using simple random sampling technique. The data collection method used is the scale of social support and learning motivation. The data analysis technique used is the Product Moment correlation statistical test. The results showed that there was a significant relationship between social support and learning motivation in students in online lectures with a calculated r value of 0.720 > r table 0.197 and a sig value of 0.000 (p < 0.05) which indicates that there is a relationship. That is, the higher the social support, the higher the learning motivation, on the contrary, the lower the social support, the lower the learning motivation for students in online lectures.Dalam mengikuti perkuliahan daring, mahasiswa seringkali dihadapkan pada tantangan belajar yang berbeda dari sebelumnya, sehingga hal ini memerlukan adanya motivasi belajar yang lebih tinggi dibandingkan perkuliahan luring. Salah satu tantangan terbesar yang dihadapi oleh mahasiswa di masa pembelajaran daring adalah interaksi yang terbatas, sehingga hanya mengandalkan jaringan internet dalam menyelesaikan tugas-tugas. Dengan interaksi yang terbatas, mahasiswa sulit melakukan diskusi dan pembelajaran yang kurang bisa dipahami, sehingga hal ini menyebabkan mereka kurang termotivasi dalam belajar. Penelitian ini bertujuan untuk mengetahui hubungan dukungan sosial terhadap motivasi belajar pada mahasiswa dalam perkuliahan daring. Metode penelitian ini menggunakan pendekatan kuantitatif. Subjek dalam penelitian ini adalah 100 mahasiswa Fakultas Ilmu Sosial dan Ilmu Politik Universitas Mulawarman angkatan 2018, 2019, 2020, 2021 yang dipilih dengan menggunakan teknik simple random sampling. Metode pengumpulan data yang digunakan adalah dengan skala dukungan sosial dan motivasi belajar. Teknik analisis data yang digunakan adalah uji statistik korelasi Product Moment. Hasil penelitian menunjukkan bahwa terdapat hubungan yang signifikan antara dukungan sosial dengan motivasi belajar pada mahasiswa dalam perkuliahan daring dengan nilai r hitung 0.720 > r tabel 0.197 dan nilai sig 0.000 (p < 0.05) yang menunjukkan bahwa ada hubungan. Artinya, semakin tinggi dukungan sosial, maka semakin tinggi motivasi belajar, sebaliknya jika semakin rendah dukungan sosial, maka semakin rendah motivasi belajar motivasi belajar pada mahasiswa dalam perkuliahan daring.